AN ANALYSIS OF DIRECTIVE ELEMENTS PERFORMED IN FILM “THE EXORCIST” (Conference on English Language Teaching, 2023)
Every utterance of speaker always has a social purpose. An utterance in the communication contains more than one meaning or force. This research aims to identify kinds of directive elements contained in film The Exorcist. The researcher use qualitative research method in collecting and analyzing the data. The type of qualitative research will be use in this research focus on description, so it can be understood and concluded easily. The process of collecting the data consists of the researcher watched film “The Exorcist” in order to have deep understanding of the plot of the story to confirm the original dialogue of the script with the dialogue spoken by the characters, reading and identifying the directives from the film and scripts, also collecting the directives from the script. The result of analysis showed that there were six kinds of directive elements found which are; Requestive, Question, Requirement, Permissive, Prohibitive, and Advisories. These kinds of directive are also divided into some sub-categories. The precentage showed that the most dominantly used category of directive elements  in film The Exorcist is Questions with 62 utterances (46.27%), second used category of directive elements  is Requestives with 23 utterances (17.16%), third used category of directive elements  is Requirement with 18 utterances (13.43%), fourth used category of directive elements  is Advisories with 17 utterances (12.68%), and according to the chart as well, the least used category of directive elements are Permitting with 7 utterances (5.23%) and Prohibitive with 7 utterances (5.23%).